Peran Kreativitas Guru dalam Menciptakan Lingkungan Kelas yang Positif dan Produktif - Anifah Anifah (Badan Penerbit STIEPARI Press, 2025)
Teacher creativity in education is a key element that contributes to the creation of a positive and productive classroom environment. This study aims to explore how teacher creativity can influence the learning atmosphere and student interactions in the classroom. Through a qualitative approach, data was collected through interviews with teachers and direct observation in several classes at SMA Negeri 1 Lintong Nihuta. The results show that teachers who apply creative teaching methods, such as project-based learning, the use of technology, and innovative classroom arrangements, are able to increase student motivation and engagement. In addition, teacher creativity also plays a role in creating a positive relationship between teachers and students, which in turn supports students' social and emotional development. This finding highlights the importance of developing creative skills for teachers as an effort to create a better learning environment. This research is expected to provide insights for educators and policy makers in designing training programs that support creativity in teaching.